National Survey of Postsecondary Faculty (NSOPF-88): Institutional Survey Data File, 1988 ([Verlag nicht ermittelbar], 2001)
This survey collected data from institutional-level respondents on issues such as faculty composition, turnover, recruitment, retention, and tenure policies. A stratified random sample of institutions was selected from the 1987 Integrated Post-secondary Education Data System file and consisted of 480 colleges and universities. It was intended that this survey be repeated periodically, so that changes over time in faculty characteristics, behaviors, and attitudes could be assessed.